A margin for murder - Elliott, Lauren (Elliott, Lauren. Beyond the Page bookstore mystery., 2022)
"Addie ... travels to the neighboring town of Pen Hollow to attend a book sale ... But the real find is a bookmobile bus, which she's excited to refit as a traveling bookstore ... The bookmobile also holds a surprising treasure: several classic first editions and an early edition of Robert Louis Stevenson's A Child's Garden of Verses. But before the bookmobile can be delivered to Addie, a fatal car crash occurs. When an autopsy reveals poison in the victim's system and the first editions go missing, it's up to Addie to determine what would drive someone to murder"--